Transformation of Legal Communication in the Criminal Justice System in the Digital Era - Faisal Faisal; Ismadani Rofiul Ulya (Sabtida, 2026)
Legal communication is fundamental in the criminal justice system, serving as a medium for interpreting, transmitting, and implementing legal norms between law enforcement institutions and society. The reform of the Indonesian Criminal Procedure Code (KUHAP 2025) represents a strategic initiative to modernize the criminal justice system by strengthening transparency, accountability, and human rights protection in the digital era. This study employs pure normative legal research supported by a Systematic Literature Review (SLR), applying statutory, conceptual, and case-based approaches, including comparative analysis between the previous KUHAP and KUHAP 2025. Findings reveal that digital transformation has significantly reshaped legal communication by expanding interaction from formal courtroom procedures to technology-based communication between law enforcement agencies and the public. However, this transformation generates normative challenges related to data protection, technological readiness, and legal certainty in digital criminal proceedings. The study recommends standardized digital communication procedures in criminal law, strengthened data protection frameworks, and development of an integrated e-justice regulatory model. Overall, KUHAP 2025 reflects a shift toward a more transparent, adaptive, and technology-based criminal justice system grounded in constitutional values.